Mucha‐Habermann disease: a pediatric case report and proposal of a risk score. (20th July 2021) - Blohm, Martin Ernst; Ebenebe, Chinedu Ulrich; Rau, Cornelius; Escherich, Carolin; Johannsen, Jessika; Escherich, Gabriele; Driemeyer, Joenna; Nagel, Philipp Daniel; Kobbe, Robin; Lütgehetmann, Marc; Lennartz, Maximilian; Booken, Nina; et al.
Abstract: Febrile ulceronecrotic Mucha‐Habermann disease (FUMHD) is a rare inflammatory dermatological disease. A case of a 13‐year‐old boy with FUMHD possibly triggered by mycoplasma infection is presented. Based on FUMHD cases identified in a MEDLINE literature search, demographic, treatment, and outcome data were analyzed. An FUMHD mortality risk score is proposed based on the likelihood ratios of risk factors for a fatal outcome. Our FUMHD case had marked leukopenia and thrombocytopenia at admission. He recovered without systemic immunosuppressive treatment. Literature review revealed 119 FUMHD cases. Overall lethality was 14/119 (12%, CI 6–17%), and lethality in children was lower (1/54, 2%, CI 0–6%) compared to adults (13/65, 20%, CI 11–31%). Risk factors for a fatal outcome (likelihood ratio; P ) were sepsis (24.97, P < 0.001), adult vs. pediatric patient age (11.19; P = 0.001), systemic involvement (19.97, P < 0.001), and mucosal involvement (4.58; P = 0.032). The proposed FUMHD mortality risk score = Age/10 + 4 + 4 (if systemic involvement) + 1 (if mucosal involvement) was discriminative (sensitivity 93%, specificity 77%). In FUMHD, immune‐suppressive treatment intensity should be balanced against the mortality risk, as infectious complications are a frequent cause of death.